Validation of a Motion-Robust 2D Sequential Technique for Quantification of Hepatic Proton Density Fat Fraction during Free Breathing - Pooler, B. Dustin (J Magn Reson Imaging, 2018)
BACKGROUND: Current chemical-shift encoded (CSE) MRI techniques for measuring hepatic proton density fat fraction (PDFF) are sensitive to motion artifacts. PURPOSE: Initial validation of a motion-robust 2D-sequential CSE-MRI technique for quantification of hepatic PDFF. STUDY TYPE: Phantom study and prospective in vivo cohort. POPULATION: 50 adult patients (27 women, 23 men, mean age 57.2 years). FIELD STRENGTH/SEQUENCE: 3D, 2D-interleaved, and 2D-sequential CSE-MRI acquisitions at 1.5T. ASSESSMENT: Three CSE-MRI techniques (3D, 2D-interleaved, 2D-sequential) were performed in a PDFF phantom and in vivo. Reference standards were 3D CSE-MRI PDFF measurements for the phantom study and single voxel MR spectroscopy hepatic PDFF measurements (MRS-PDFF) in vivo. In vivo hepatic MRI-PDFF measurements were performed during a single breath hold (BH) and free breathing (FB), and were repeated by a second reader for the FB 2D-sequential sequence to assess inter-reader variability. STATISTICAL TESTS: Correlation plots to validate the 2D-sequential CSE-MRI against the phantom and in vivo reference standards. Bland-Altman analysis of FB versus BH CSE-MRI acquisitions to evaluate robustness to motion. Bland-Altman analysis to assess inter-reader variability. RESULTS: Phantom 2D-sequential CSE-MRI PDFF measurements demonstrated excellent agreement and correlation (R(2)>0.99) with 3D CSE-MRI. In vivo, the mean (±SD) hepatic PDFF was 8.8±8.7% (range 0.6–28.5%). Compared with BH acquisitions, FB hepatic PDFF measurements demonstrated bias of +0.15% for 2D-sequential compared with +0.53% for 3D and +0.94% for 2D-interleaved. 95% limits of agreement (LOA) were narrower for 2D-sequential (±0.99%), compared with 3D (±3.72%) and 2D-interleaved (±3.10%). All CSE-MRI techniques had excellent correlation with MRS (R(2)>0.97). The FB 2D-sequential acquisition demonstrated little inter-reader variability, with mean bias of +0.07% and 95% LOA of ±1.53%. CONCLUSIONS: This motion-robust 2D-sequential CSE-MRI can accurately measure hepatic PDFF during free breathing in a patient population with a range of PDFF values of 0.6–28.5%, permitting accurate quantification of liver fat content without the need for suspended respiration.